A simple and environmental strategy to separate and purify dye-contaminated emulsion using waste porous honeycomb cinder. Issue 7 (1st June 2022) - He, Linyi; Long, Mengying; Miao, Xinrui; Zhou, Qiannan; Dong, Meiqiu; Liu, Xiaogang; Deng, Wenli
Abstract: Numerous superwetting materials have been designed to separate water-in-oil emulsions, however, it still remains challenge to realize emulsion separation and dye adsorption simultaneously. In this work, we adopt a simple strategy to remove dyes and tiny water droplets from the dyed surfactant-stabilized water-in-oil emulsion using layer-stacked waste honeycomb cinder (WHC). The layer-stacked WHC with under-oil superhydrophilicity is obtained to separate the dyed emulsions only driven by gravity. The volumetric water fraction of the emulsion is 1%. The WHC displays exceptional separation efficiency and high filtrate flux for the emulsion separation, and highly efficient adsorption for various kinds of dyes in water, oil, and emulsion. Interestingly, no tiny water droplets in the filtrate are detected by dynamic light scattering (DLS), even though the concentration of surfactant in the emulsion is up to 2.4 mg/mL. Furthermore, the WHC could remain considerable recyclability after 10 cycles of emulsion separation. The separation efficiency could be improved after the WHC is immersed in corrosive liquid, which shows the excellent chemical durability of the WHC. This work demonstrates that the WHC as green and sustainable material can be efficiently reused to separate emulsions and adsorb dyes. Graphical Abstract: